Molecular Structure of Photosynthetic Microbial Biofuels for Improved Engine Combustion and Emissions Characteristics - Hellier, Paul; Purton, Saul; Ladommatos, Nicos (Frontiers in Bioengineering and Biotechnology, 2015)
The metabolic engineering of photosynthetic microbes for production of novel hydrocarbons presents an opportunity for development of advanced biofuels that are significantly more sustainable, throughout the production-to-consumption lifecycle, than the fossil fuels and crop based biofuels they might replace. Current biofuels, such as bioethanol and fatty acid methyl esters, have been developed primarily as drop-in replacements for existing fossil fuels, based on their physical properties and autoignition characteristics under specific combustion regimes. However, advances in the genetic engineering of microalgae and cyanobacteria, and the application of synthetic biology approaches offer the potential of designer strains capable of producing hydrocarbons and oxygenates with specific molecular structures designed for higher efficiency of energy release and lower exhaust emissions during combustion. This paper presents a review of potential fuel molecules from photosynthetic microbes and the performance of these possible fuels in modern internal combustion engines, highlighting which modifications to the molecular structure of such fuels may enhance the suitability of these for specific combustion regimes.